Cochlear implantation in patients with vestibular schwannoma: A single United Kingdom center experience. (24th April 2013) - Pai, Irumee; Dhar, Vikram; Kelleher, Catherine; Nunn, Terry; Connor, Steve; Jiang, Dan; O'Connor, Alec Fitzgerald
Abstract : Objectives/Hypothesis: To evaluate the outcome of cochlear implantation (CI) in patients with vestibular schwannoma (VS). Study Design: A retrospective case series from a tertiary auditory implant center. Methods: A retrospective case note review was carried out to evaluate patients with bilateral profound hearing loss and VS who underwent unilateral CI within the Auditory Implant Centre at St. Thomas' Hospital, London, between 2000 and 2012. This included both bilateral VS with neurofibromatosis type 2 (NF2) and unilateral sporadic VS. Outcome measures included speech perception with Bamford‐Kowal‐Bench and City University of New York sentences, sound‐field thresholds with warble tones, and the subjective benefits reported by patients. Results: The study included five patients with NF2 and bilateral VS and two patients with sporadic unilateral VS. The standard preoperative audiologic assessment for CI often could not be carried out in NF2 patients. Preoperative testing was more complete in the two patients with sporadic VS. The audiologic outcome was variable. Open‐set speech perception was achieved in three out of five NF2 patients, and another reported significant improvement in environmental sound perception and ease of communication. The outcome was overall better in patients with sporadic VS, both of whom were able to use the telephone in their implanted ear. Conclusions: Good speech perception can be achieved in some cases, and CI should be considered as an option for auditory rehabilitation in patients with VS. Level of Evidence: 4. Laryngoscope, 123:2019–2023, 2013